2021
DOI: 10.3390/cells10102687
|View full text |Cite
|
Sign up to set email alerts
|

Clinical Applications of Cell-Scaffold Constructs for Bone Regeneration Therapy

Abstract: Bone tissue engineering (BTE) is a process of combining live osteoblast progenitors with a biocompatible scaffold to produce a biological substitute that can integrate into host bone tissue and recover its function. Mesenchymal stem cells (MSCs) are the most researched post-natal stem cells because they have self-renewal properties and a multi-differentiation capacity that can give rise to various cell lineages, including osteoblasts. BTE technology utilizes a combination of MSCs and biodegradable scaffold mat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
29
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 28 publications
(29 citation statements)
references
References 109 publications
(168 reference statements)
0
29
0
Order By: Relevance
“…Osteoblasts derived from multipotent MSCs are critical players in bone formation and repair [30]. During bone healing, osteoblasts can proliferate and deposit bone ECM components in the injury sites [31]. Several studies have demonstrated that primary osteoblast cultures can heal bone defects, which has been suggested as a potential approach for bone defect therapy [32][33][34] In this research, the primary osteoblasts of both groups were separated and cultured in osteogenic medium, and weakened ALP staining and decreased expression levels of osteogenic marker genes were observed in the culture aggregates of the S89G-DMP1 mice.…”
Section: Discussionmentioning
confidence: 99%
“…Osteoblasts derived from multipotent MSCs are critical players in bone formation and repair [30]. During bone healing, osteoblasts can proliferate and deposit bone ECM components in the injury sites [31]. Several studies have demonstrated that primary osteoblast cultures can heal bone defects, which has been suggested as a potential approach for bone defect therapy [32][33][34] In this research, the primary osteoblasts of both groups were separated and cultured in osteogenic medium, and weakened ALP staining and decreased expression levels of osteogenic marker genes were observed in the culture aggregates of the S89G-DMP1 mice.…”
Section: Discussionmentioning
confidence: 99%
“…While the use of free MSC has not yielded consistent success in repairing damaged tissues, using them in constructs generated in vitro has led to some successes for some tissues. MSC isolated from a variety of tissues have been isolated and then often incorporated into synthetic scaffolds, scaffolds with other ECM-like matrix components, an endogenous natural protein matrix or a hybrid synthetic/natural matrix, reviewed in [ 156 , 157 , 158 , 159 ]. Recent advances in bioprinting may offer more sophisticated and complex scaffold-cell constructs [ 160 , 161 , 162 ].…”
Section: Use Of Msc In Tissue Engineered Constructs To Enhance Repair...mentioning
confidence: 99%
“…Critical-size bone defects (CSDs) are treated with regenerative therapy using bone grafting, and a variety of prosthetic bone materials have been developed in this field. One that does not heal naturally throughout a patient's lifetime and requires surgical stabilisation and additional surgical intervention is what is meant by a defect, according to definition [ 5 ]. An ideal bone graft must be biocompatible, biodegradable, osteoconductive, osteoinductive, structurally similar to bone, easy to use, and cost-effective.…”
Section: Reviewmentioning
confidence: 99%
“…Because of collagen (Coll) degradation, PLLA/Coll scaffolds had a fractured morphology after 80 days [ 20 ]. In order to predictably restore the confused architecture and function of bone, functional BTE essentially uses osteoprogenitors obtained from mesenchymal stem cells (MSCs) and seeded onto a scaffold [ 5 ]. MSCs produced from embryonic stem cells (ESCs) or induced pluripotent stem cells (iPSCs) may be a new source for BTE studies [ 21 ].…”
Section: Reviewmentioning
confidence: 99%
See 1 more Smart Citation